Subchondral Bone Trabecular Integrity Predicts and Changes Concurrently With Radiographic and Magnetic Resonance Imaging–Determined Knee Osteoarthritis Progression. Issue 7 (2nd July 2013) - Kraus, Virginia Byers; Feng, Sheng; Wang, ShengChu; White, Scott; Ainslie, Maureen; Graverand, Marie‐Pierre Hellio Le; Brett, Alan; Eckstein, Felix; Hunter, David J.; Lane, Nancy E.; Taljanovic, Mihra S.; Schnitzer, Thomas; et al.
Abstract : Objective: To evaluate subchondral bone trabecular integrity (BTI) on radiographs as a predictor of knee osteoarthritis (OA) progression. Methods: Longitudinal (baseline, 12‐month, and 24‐month) knee radiographs were available for 60 female subjects with knee OA. OA progression was defined by 12‐ and 24‐month changes in radiographic medial compartment minimal joint space width (JSW) and medial joint space area (JSA), and by medial tibial and femoral cartilage volume on magnetic resonance imaging. BTI of the medial tibial plateau was analyzed by fractal signature analysis using commercially available software. Receiver operating characteristic (ROC) curves for BTI were used to predict a 5% change in OA progression parameters. Results: Individual terms (linear and quadratic) of baseline BTI of vertical trabeculae predicted knee OA progression based on 12‐ and 24‐month changes in JSA ( P < 0.01 for 24 months), 24‐month change in tibial ( P < 0.05), but not femoral, cartilage volume, and 24‐month change in JSW ( P = 0.05). ROC curves using both terms of baseline BTI predicted a 5% change in the following OA progression parameters over 24 months with high accuracy, as reflected by the area under the curve measures: JSW 81%, JSA 85%, tibial cartilage volume 75%, and femoral cartilage volume 85%. Change in BTI was also significantly associated ( P < 0.05) with concurrent change in JSA over 12 and 24 months and with change in tibial cartilage volume over 24 months. Conclusion: BTI predicts structural OA progression as determined by radiographic and MRI outcomes. BTI may therefore be worthy of study as an outcome measure for OA studies and clinical trials.